2013
DOI: 10.14260/jemds/543
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiogram of Extended Spectrum Beta-Lactamase Producing Escherichia Coli

Abstract: BACKGROUND: Beta lactams are the most extensively used group of antimicrobials, however growing resistance to these invaluable drugs mediated by extended spectrum beta-lactamase (ESBL) enzymes is a major concern. The frequency of ESBL producing strains among clinical isolates has been steadily increasing over the past few years that has generated a major problem in clinical therapeutics. OBJECTIVES: Our aim was to determine the prevalence of ESBL producing Escherichia coli, study their antibiogram and to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Lower resistance rates to ciprofloxacin, usually prescribed in uncomplicated UTI and other infections, have been reported in Nepal (45%) [ 6 ], in India (52.80%) [ 23 ] and in Iran (60%) [ 20 ]. It was showed that uncontrolled use of quinolones in the past years led to a growing resistance to these antibiotics particularly to ciprofloxacin worldwide [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower resistance rates to ciprofloxacin, usually prescribed in uncomplicated UTI and other infections, have been reported in Nepal (45%) [ 6 ], in India (52.80%) [ 23 ] and in Iran (60%) [ 20 ]. It was showed that uncontrolled use of quinolones in the past years led to a growing resistance to these antibiotics particularly to ciprofloxacin worldwide [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%